Negative electrode for lithium metal battery, method for manufacturing the same, and lithium metal battery containing the same
By forming a protective layer composed of metal powder, metal wire, or alloyable metal powder, and wire on the negative electrode of the lithium metal battery, the problems of the reaction between lithium metal and atmospheric and deterioration of the life characteristics of the electrodeposited layer are solved, and the effects of reducing resistance and improving battery life are achieved.
Patent Information
- Application Number
- CN202180007091.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-28
- Filing Date
- 2021-11-01
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-11-01
AI Technical Summary
In lithium metal batteries, when lithium metal is used as the negative electrode material, the density is low and the standard reduction potential is extremely low, resulting in rapid deterioration of the life characteristics of the electrodeposited layer during assembly.
In the negative electrode of the lithium metal battery, a lithium metal layer is formed on the metal current collector substrate and a protective layer is formed thereon. The protective layer is composed of metal powder, metal wire, alloyable metal powder or alloyable metal wire to reduce reaction with the atmosphere and side reaction of the electrolyte.
By forming a protective layer, the reaction between lithium metal and the atmosphere is reduced, the resistance is reduced, and the density of the lithium battery deposited layer and the life characteristics of the battery are improved.
Smart Images

Figure GDA0003688324690000231
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2020-0144667 filed on November 2, 2020, and Korean Patent Application No. 10-2021-0146015 filed on October 28, 2021, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein in their entireties by reference.
[0003] The present disclosure relates to a negative electrode for a lithium metal battery, a method for manufacturing the negative electrode, and a lithium metal battery including the negative electrode. Background Art
[0004] Due to the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative or clean energy, among which the most active research areas are the power generation and storage using electrochemistry.
[0005] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to be gradually expanded.
[0006] Recently, with the increase in technology development and demand for mobile devices such as portable computers, portable phones and cameras, the demand for secondary batteries as energy sources has also increased rapidly. Among them, such secondary batteries are lithium secondary batteries that exhibit high charge / discharge characteristics and life characteristics and are environmentally friendly, in which many studies have been conducted and are now commercialized and widely used.
[0007] Generally, the secondary battery has a structure in which a non-aqueous electrolyte is impregnated into an electrode assembly including a positive electrode, a negative electrode and a porous separator. In addition, the positive electrode is generally manufactured by coating a positive electrode mixture containing a positive electrode active material on an aluminum foil, and the negative electrode is manufactured by coating a negative electrode mixture containing a negative electrode active material on a copper foil.
[0008] Generally, the positive electrode active material uses a lithium transition metal oxide, and the negative electrode active material uses a carbon-based material.
[0009] However, recently, lithium metal batteries using lithium metal itself, which exhibits high energy density, as a negative electrode active material have been commercialized.
[0010] At this time, because the density of the lithium metal used as the negative electrode is low (0.54 g / cm 3) and a very low standard reduction potential (-3.045V SHE: standard hydrogen electrode), so it has become a material of great interest as a negative electrode material for high energy density batteries. In addition, despite the problems caused by very high chemical activity, in recent years, with the steady increase in the use of mobile communications and portable electronic devices and their rapid development, the demand for developing secondary batteries with high energy density has continued to increase. Therefore, the necessity of using lithium metal negative electrodes continues to emerge.
[0011] In this case, when a lithium metal electrode is used as the negative electrode, the lithium metal has very excellent reactivity, so that it will react with the atmosphere and disintegrate during the assembly of the secondary battery, and the lithium electrodeposition layer formed by charging will cause serious side reactions due to direct contact with the electrolyte, which leads to rapid deterioration of life characteristics.
[0012] Therefore, it is necessary to develop a negative electrode that can solve the above problems and thus can be used in lithium metal batteries. Summary of the invention
[0013] [Technical issues]
[0014] The present disclosure is intended to solve the above-mentioned problems and other technical problems that have not yet been solved.
[0015] Specifically, an object of the present disclosure is to provide a negative electrode capable of reducing resistance by minimizing a reaction of the negative electrode with the atmosphere during assembly of the secondary battery.
[0016] Another object of the present disclosure is to minimize the thickness of the lithium electrodeposition layer formed during the operation of a lithium metal battery using the negative electrode, increase the electrodeposition density, and prevent the side reaction of the electrolyte, thereby improving the life characteristics.
[0017] [Technical solution]
[0018] In order to achieve the above object, according to one embodiment of the present disclosure, a negative electrode for a lithium metal battery is provided, the negative electrode comprising:
[0019] a metal current collector substrate, a lithium metal layer formed on at least one surface of the metal current collector substrate, and a protective layer formed on the lithium metal layer,
[0020] The protective layer comprises: metal powder or metal wire; alloyable metal powder or alloyable metal wire; or a mixture thereof.
[0021] The metal current collector substrate may be one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper surface-treated with a dissimilar metal, stainless steel surface-treated with a dissimilar metal, and aluminum-cadmium alloy.
[0022] The metal current collector substrate may be copper.
[0023] In a specific embodiment, the lithium metal layer may have a thickness of 1 to 100 μm.
[0024] In a specific embodiment, the metal powder or the metal wire may include a metal selected from the group consisting of copper, stainless steel, nickel, titanium, calcined carbon, and exotic metals, and in particular, it may include metallic copper or metallic nickel.
[0025] Furthermore, the alloyable metal powder or alloyable metal wire may contain an alloyable metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd and Hg.
[0026] In a specific embodiment, the diameters of the metal powder and the alloyable metal powder of the protective layer can be 1nm~30μm, the diameters of the metal wire and the alloyable metal wire of the protective layer can be 1nm~30μm, and their respective aspect ratios (wire length / wire diameter) can be greater than 3.
[0027] In a specific embodiment, the protective layer may be a mixture of metal powder or metal wire and alloyable metal powder or alloyable metal wire.
[0028] In a specific embodiment, the protective layer may have a thickness of 0.1 μm to 100 μm, and the protective layer may have a porosity of 1% to 70%.
[0029] The protective layer may further include an adhesive and a conductive material.
[0030] According to another embodiment of the present disclosure, there is provided a method for manufacturing a negative electrode according to item 1, the method comprising the following steps:
[0031] (a) forming a lithium metal layer on at least one surface of a metal current collector substrate;
[0032] (b) mixing metal powder or metal wire, alloyable metal powder or alloyable metal wire or a mixture thereof with a solvent to prepare a slurry; and
[0033] (c) coating the slurry on the lithium metal in step (a) and drying to form a protective layer, thereby manufacturing a negative electrode,
[0034] The powder or filament of step (b) has a diameter of 1 μm to 30 μm.
[0035] According to another embodiment of the present disclosure, there is provided a method for manufacturing a negative electrode according to item 1, the method comprising the following steps:
[0036] (a) forming a lithium metal layer on at least one surface of a metal current collector substrate;
[0037] (b) dispersing metal powder or metal wire, alloyable metal powder or alloyable metal wire or a mixture thereof in a solvent to prepare a dispersion; and
[0038] (c) coating the dispersion on the lithium metal in step (a) and drying to form a protective layer, thereby manufacturing a negative electrode,
[0039] The powder or wire of step (b) has a diameter of 1 nm to 1000 nm.
[0040] In this case, the slurry or dispersion may be prepared such that the solid content of the metal powder, metal wire, alloyable metal powder or alloyable metal wire in the slurry or dispersion accounts for 0.1 to 80 volume % based on the total volume of the slurry or dispersion.
[0041] According to yet another embodiment of the present disclosure, there is provided a lithium metal battery, wherein an electrode assembly is constructed in a battery case together with a lithium non-aqueous electrolyte, wherein the electrode assembly comprises:
[0042] The negative electrode according to item 1;
[0043] a positive electrode having a structure in which a positive electrode mixture containing an active material is coated on at least one surface of a positive electrode current collector; and
[0044] A separator is disposed between the negative electrode and the positive electrode.
[0045] In this case, the negative electrode may further include a lithium electrodeposition layer formed by precipitating lithium on the protective layer, and the thickness of the lithium electrodeposition layer may be 0.1 to 90 μm. DETAILED DESCRIPTION
[0046] Hereinafter, the present disclosure will be described in more detail for better understanding of the present disclosure.
[0047] The terms or words used in the present specification and claims should not be construed as limited to common or dictionary terms, and the present disclosure should be interpreted using meanings and concepts consistent with the technical ideas of the present disclosure, based on the principle that inventors can appropriately define the concepts of the terms to appropriately describe their own inventions in the best manner.
[0048] The technical terms provided herein are only used for the purpose of describing specific embodiments and are not intended to limit the present disclosure. Unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include the plural forms as well.
[0049] Furthermore, throughout the specification, when a part is referred to as “comprising” a specific component, unless otherwise specified, it means that the part may further include other components, rather than excluding the other components.
[0050] According to one embodiment of the present disclosure, a negative electrode for a lithium metal battery is provided, the negative electrode comprising: a metal current collector substrate, a lithium metal layer formed on at least one surface of the metal current collector substrate, and a protective layer formed on the lithium metal layer, wherein the protective layer comprises: metal powder or metal wire; alloyable metal powder or alloyable metal wire; or a mixture thereof.
[0051] Here, the alloyable metal refers to a metal that can form an alloy with lithium. In addition, the dissimilar metal may be at least one selected from the group consisting of Cu-Ni, Ti-Ni, Cu-Al, Cu-Zn, Sn-Al and Si-Ag.
[0052] The metal current collector substrate may be one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper surface-treated with a dissimilar metal, stainless steel surface-treated with a dissimilar metal, and aluminum-cadmium alloy.
[0053] The metal current collector substrate may be copper.
[0054] The lithium metal layer is a negative electrode active material, and its thickness and amount can be determined according to the desired purpose, but is not limited thereto. For example, it can have a thickness of 1 to 100 μm, particularly 5 to 70 μm, and more particularly 10 to 50 μm.
[0055] When the thickness is too thin and outside the above range, lithium as an active material is insufficient, and when the thickness is too thick, the lithium electrodeposition layer is subsequently formed during the charge and discharge of the secondary battery and acts as an active material. Therefore, the energy density relative to the volume may be further reduced, so it is most preferable to satisfy the above range.
[0056] However, as described above, the negative electrode formed with only such a lithium metal layer has high reactivity to the atmosphere during assembly, and when lithium is electrodeposited by charging and discharging, there is a problem that a lithium layer with a low electrodeposition density is formed, the side reaction of the electrolyte becomes excessive, and a sharp deterioration of the life characteristics occurs. This is because the lithium metal layer has a low affinity for lithium and the electrodeposition is uneven when lithium is electrodeposited.
[0057] In order to solve these problems, according to the present embodiment, a protective layer having grain boundaries can be formed as a thin layer on the lithium metal layer, thereby increasing the specific surface area and reducing the resistance. Subsequently, when lithium is electrodeposited by charging and discharging, a lithium electrodeposition layer with a high electrodeposition density can be formed.
[0058] The metal powder or metal wire contained in the protective layer may include a metal selected from the group consisting of copper, stainless steel, nickel, titanium, calcined carbon, and a dissimilar metal, and specifically, it may include metal copper or metal nickel.
[0059] Furthermore, the alloyable metal powder or alloyable metal wire may contain an alloyable metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, As, Sb, Bi, Ag, Zn, Cd and Hg, specifically, it may contain alloyable metal Al or Si.
[0060] In this way, the present disclosure may include the metal or the alloyable metal in the form of powder or wire, specifically, in the case where the protective layer is composed of only the alloyable metal, lithium is alloyed / de-alloyed in the alloyable metal, and the alloyable metal is insulated by a side reaction with the electrolyte and may be converted into a by-product having a high resistance, thereby in order to maintain the protective layer even when the alloyable metal is consumed, it contains a mixture of the metal powder or metal wire and the alloyable metal powder or alloyable metal wire, more specifically, it may be composed of a mixture.
[0061] When the protective layer is composed of a mixture, the metal powder or metal wire may be mixed with the alloyable metal powder or alloyable metal wire in a ratio of 1:99 to 99:1, specifically 1:9 to 9:1, more specifically 3:7 to 7:3 based on their weights.
[0062] On the other hand, it is preferred that the protective layer contains the metal or alloyable metal in a powder form and / or a wire form, thereby being in a form having grain boundaries and having a predetermined number or more of pores.
[0063] At this time, the diameter of the metal powder or alloyable metal powder of the protective layer may be 1 nm to 30 μm. In addition, the diameter of the metal wire of the protective layer and the alloyable metal wire may be 1 nm to 30 μm, and their aspect ratios (wire length / wire diameter) may be 3 or more, specifically 3 or more and 2000 or less.
[0064] The form that the diameter is too small and outside the above range is difficult to manufacture, and if the diameter is too large and outside the above range, the effect of increasing the specific surface area is not significant, so this is not preferred. If the aspect ratio of the filament is too large, it is difficult to form a protective layer, and if the aspect ratio is too small, it is no different from powder.
[0065] In this case, the diameter is the average diameter (D50), which refers to the particle diameter corresponding to the 50% point in the cumulative distribution of the number of particles relative to the particle diameter. That is, D50 is the particle diameter corresponding to the 50% point in the cumulative distribution of the number of particles relative to the particle diameter.
[0066] This can be measured using a laser diffraction method. Specifically, the powder to be tested is dispersed in a dispersion medium and then introduced into a commercially available laser diffraction particle size analyzer (e.g., Microtrac S3500). As the particles pass through the laser beam, the diffraction pattern is measured as a function of particle size to calculate the particle size distribution. The D50 can be measured by calculating the particle size corresponding to 50% of the points in the cumulative distribution of the number of particles relative to the particle size in the analyzer.
[0067] The aspect ratio is a value obtained by dividing the length of the wire by the D50, wherein the length of the wire is obtained by taking an SEM photograph and arbitrarily specifying 10 to 100 formed metal or alloyable metal wires and calculating the average value thereof.
[0068] When the protective layer having grain boundaries is included in this manner, the specific surface area of the negative electrode current collector increases, the number of sites where lithium ions generated by charge and discharge can be electrodeposited increases, and subsequently, a lithium electrodeposition layer having improved electrodeposition density can be obtained.
[0069] As another configuration, such a protective layer is formed in a relatively thin range, so as not to reduce the energy density of the lithium metal battery relative to the volume. Thus, the protective layer can specifically have a thickness of 0.1 μm to 100 μm, specifically a thickness of 1 μm to 60 μm, and more specifically a thickness of 1 μm to 50 μm.
[0070] When the protective layer is formed too thick and outside the above range, a large amount of lithium is embedded in such protective layer, whereby the lithium electrodeposition layer obtained by electrodeposition cannot be sufficiently obtained, and high energy density cannot be obtained. When the protective layer is formed too thin, it is not preferred because the effect of improving the lithium electrodeposition density accompanying charge and discharge, which is the effect expected by the present disclosure, cannot be obtained.
[0071] For such a protective layer, the interface resistance becomes larger when the porosity is too small. Therefore, it is preferred that the porosity is at least 1% or more, specifically 10% or more, and more specifically 20% or more. In order to make the protective layer have a specific strength and reduce the thickness of the lithium electrodeposition layer through an alloyable mechanism, at least a certain amount of the metal or alloyable metal is required, and thus, the porosity is preferably 70% or less, specifically 60% or less, and more specifically 50% or less. This porosity may vary with solid content, drying conditions, manufacturing method, etc. Specifically, when prepared using a slurry as follows, it can be formed in the range of 20% to 70%, and when prepared using a dispersion, it can be formed in the range of 1% to 30%.
[0072] On the other hand, in the absence of an adhesive, the protective layer can supplement the effect of the adhesive by coating, drying and calendering, and the protective layer itself is a metal material, and thus may not contain a conductive material. However, when the thickness of the protective layer becomes thicker, an adhesive for further bonding them and a conductive material for enhancing conductivity may be additionally contained.
[0073] Specific examples of the binder may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof. The metal and alloyable metal of the protective layer and the binder may be contained in a ratio of 7:3 to 99:1 based on their weight.
[0074] When the content of the binder is too large and not within the above range, it is difficult to fully demonstrate the effect of improving the electrodeposition density of the lithium electrodeposition layer by forming the protective layer. When the content of the binder is too small, the combination with the lithium metal layer cannot be performed well, which is not preferred.
[0075] There is no particular limitation on the conductive material as long as it has high conductivity without causing chemical changes in the corresponding battery, and for example, graphite such as natural graphite and artificial graphite; carbon blacks such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; fluorocarbon powders; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives. In this case, the metal and alloyable metal of the protective layer and the conductive material may be contained in a ratio of 7:3 to 99:1 based on their weight.
[0076] According to another embodiment of the present disclosure, there is provided a method for manufacturing a negative electrode, the method comprising the following steps:
[0077] (a) forming a lithium metal layer on at least one surface of a metal current collector substrate;
[0078] (b) mixing metal powder or metal wire, alloyable metal powder or alloyable metal wire, or a mixture thereof with a solvent to prepare a slurry; and
[0079] (c) coating the slurry on the lithium metal in step (a) and drying to form a protective layer, thereby manufacturing a negative electrode,
[0080] The powder or filament of step (b) has a diameter of 1 μm to 30 μm.
[0081] According to another embodiment of the present disclosure, there is provided a method for manufacturing a negative electrode, the method comprising the following steps:
[0082] (a) forming a lithium metal layer on at least one surface of a metal current collector substrate;
[0083] (b) dispersing metal powder or metal wire, alloyable metal powder or alloyable metal wire, or a mixture thereof in a solvent to prepare a dispersion; and
[0084] (c) coating the dispersion on the lithium metal in step (a) and drying to form a protective layer, thereby manufacturing a negative electrode,
[0085] The powder or wire of step (b) has a diameter of 1 nm to 1000 nm.
[0086] That is, in the manufacturing method, the protective layer is formed by coating on the lithium metal layer formed on at least one surface of the metal current collector substrate, but the manufacturing method varies depending on the diameter of the metal or alloyable metal powder or wire contained in the protective layer.
[0087] Specifically, when the diameter is relatively large, it can be made into a slurry form and coated on the lithium metal layer. When the diameter is small, it can be manufactured by preparing a pre-dispersion containing metal or alloyable metal powder or wire and coating it on the lithium metal layer, as in the method of preparing a pre-dispersion of a conductive material.
[0088] The diameter is, as mentioned above, the average diameter (D50) of the particles.
[0089] Specifically, the powder or wire may have a diameter of 0.01 μm to 10 μm, more specifically 0.1 μm to 5 μm.
[0090] In the manufacturing method as described above, in order to satisfy the effect according to the present disclosure, it is more preferable to adjust the porosity as described above, whereby the slurry or dispersion can be prepared so that the solid content of the metal powder, metal wire, alloyable metal powder or alloyable metal wire contained in the solvent accounts for 0.1 to 80% by volume of the total volume of the slurry or the dispersion. More specifically, the slurry is prepared so that the solid content of the slurry accounts for 30 to 80% by volume of the total volume of the slurry, or the dispersion is prepared so that the solid content of the dispersion accounts for 0.1 to 30% by weight of the total volume of the dispersion, and then the prepared slurry or dispersion can be applied and dried to adjust the porosity.
[0091] The specific types of the metal powder or metal wire, the alloyable metal powder or the alloyable metal wire are the same as those described above.
[0092] On the other hand, the lithium metal layer may be formed by a method such as vapor deposition or electrodeposition.
[0093] According to another embodiment of the present disclosure, a lithium metal battery is provided, wherein an electrode assembly is constructed together with a lithium non-aqueous electrolyte in a battery case, wherein the electrode assembly comprises: the negative electrode; a positive electrode having a structure in which a positive electrode mixture comprising active materials is coated on at least one surface of a positive electrode collector; and a separator disposed between the negative electrode and the positive electrode.
[0094] The positive electrode has a structure in which a positive electrode mix including an active material is coated on at least one surface of a positive electrode current collector.
[0095] There is no particular limitation on the positive electrode current collector as long as it has conductivity without causing chemical changes to the battery, and for example: stainless steel; aluminum; nickel; titanium; calcined carbon; or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector may have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesion of the positive electrode active material. For example, it may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0096] The positive electrode active material as the active material may include, for example: a layered compound such as lithium nickel oxide (LiNiO2) or a compound substituted by one or more transition metals; a lithium manganese oxide such as a chemical formula Li 1+x Mn 2-x O4 (where x = 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7; 1-x M x Ni-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); represented by the chemical formula LiMn 2-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M = Fe, Co, Ni, Cu or Zn); LiNi x Mn 2-x O4; LiMn2O4, wherein a portion of Li in the chemical formula is replaced by an alkaline earth metal ion; a disulfide compound; Fe2(MoO4)3, etc., but not limited thereto.
[0097] The positive electrode mixture may further include a conductive material and a binder in addition to the positive electrode active material.
[0098] The conductive material is generally added in an amount of 0.1 to 30% by weight, specifically 1 to 10% by weight, and more specifically 1 to 5% by weight, based on the total weight of the positive electrode mixture layer. The conductive material is not particularly limited as long as it has high conductivity without causing chemical changes in the corresponding battery, and for example: graphite such as natural graphite and artificial graphite; carbon blacks such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; fluorocarbon powders; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives.
[0099] The binder is a component that helps to bind the active material, the conductive material, etc. and to the current collector, and based on the total weight of the positive electrode mixture, the general addition amount can be 0.1 to 30% by weight, specifically 1 to 10% by weight, and more specifically 1 to 5% by weight. Examples of the binder may include polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, various copolymers, etc.
[0100] The separator is an insulating film with high ion permeability and mechanical strength. The pore size of the separator is generally 0.01 to 10 μm, and the thickness is generally 5 to 300 μm. As such a separator, for example: chemically resistant and hydrophobic olefin polymers such as polypropylene; sheets or non-woven fabrics made of glass fiber or polyethylene are used. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte can also serve as a separator.
[0101] The lithium non-aqueous electrolyte generally includes a lithium salt and a non-aqueous solvent. As the non-aqueous solvent, a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, etc. are used, but are not limited thereto.
[0102] As examples of the nonaqueous electrolyte, there may be mentioned aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate and ethyl propionate.
[0103] Examples of the organic solid electrolyte include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyalginate lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ion dissociative groups, and the like.
[0104] Examples of the inorganic solid electrolyte include nitrides, halides and sulfates of lithium (Li) such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, Li3PO4-Li2S-SiS2.
[0105] The lithium salt is a material that is easily soluble in the non-aqueous electrolyte. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate and lithium imide.
[0106] In addition, in order to improve the charge / discharge characteristics, flame retardancy, etc., the nonaqueous electrolyte may further contain, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted The electrolyte may further include oxazolidinone, N, N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum chloride, etc. In some cases, in order to impart incombustibility, the electrolyte may further include halogen-containing solvents such as carbon tetrachloride and trifluoroethylene. In addition, in order to improve high temperature storage characteristics, the electrolyte may further include carbon dioxide gas. In addition, it may further include fluoroethylene carbonate (FEC), propene sultone (PRS), etc.
[0107] The battery case is not particularly limited as long as it has a structure capable of accommodating the electrode assembly, and may be a pouch-type battery known in the art or a prismatic or cylindrical battery case made of a metal can.
[0108] On the other hand, the lithium metal battery is manufactured by enclosing an electrode assembly together with a lithium nonaqueous electrolyte in a battery case, sealing the case and activating the battery, wherein the negative electrode may further include a lithium electrodeposition layer due to lithium precipitation on the protective layer.
[0109] Specifically, when lithium is filled in the protective layer, the lithium first reacts with the metal or alloyable metal. For example, in the case of an alloyable metal, it causes an alloying reaction. Subsequently, after the alloying reaction is completed, lithium is electrodeposited on the alloy particles.
[0110] Therefore, according to the present disclosure, since the lithium electrodeposition layer must be included in essence, the amount of lithium provided by the positive electrode must exceed the amount that can be alloyed by, for example, Al. In other words, if the amount of lithium that the positive electrode can provide is referred to as the positive electrode loading (e.g., 5 mAh / cm 2 ), and the amount of Al that can be alloyed on the negative electrode is called the negative electrode loading (e.g. 1 mAh / cm 2 ), then the maximum is 1mAh / cm 2 Li forms Li9Al4, and 4 mAh / cm 2 A lithium electrodeposition layer is formed.
[0111] According to the present disclosure, the lithium electrodeposition layer is also used as a negative electrode active material. In the past, when the protective layer was not formed, the electrodeposition thickness of the lithium electrodeposition layer became thicker than 100 μm, and the reaction area with the electrolyte was large, and the life characteristics deteriorated rapidly. However, according to the present disclosure, because the protective layer is alloyable with lithium and the thickness of the lithium electrodeposition layer is thinned to 90 μm or less, the side reactivity with the electrolyte is reduced, which can show improved life characteristics.
[0112] More specifically, according to the present disclosure, the thickness of the lithium electrodeposition layer may be 0.1 to 90 μm, specifically 5 to 40 μm, and more specifically 10 to 30 μm.
[0113] Furthermore, by forming the protective layer as described above, the reaction of the negative electrode with the atmosphere during assembly of the secondary battery can be minimized, so that the resistance can be reduced.
[0114] Hereinafter, preferred embodiments of the present disclosure, comparative examples for comparison with them, and experimental examples for evaluating them are described. However, it will be apparent to those skilled in the art that these embodiments are for illustrative purposes only, and that various changes and variants can be made without departing from the scope and spirit of this specification, and it goes without saying that such changes and variants fall within the scope of the appended claims.
[0115] <Comparative Example 1>
[0116] A commercially available copper current collector (I2B, Iljin Materials Co.) was prepared as a metal current collector substrate.
[0117] A lithium foil (Li foil, thickness: 20 μm) was placed in a manner opposing one surface of the copper current collector, and then the current collector and the lithium foil were laminated and rolled to such an extent that they did not separate to form a lithium metal layer. Thus, a negative electrode was obtained.
[0118] <Comparative Example 2>
[0119] A commercially available copper current collector (I2B, Iljin Materials Co.) was prepared as a metal current collector substrate.
[0120] A lithium foil (Li foil, thickness: 20 μm) was placed in opposition to one surface of the copper current collector, and then the current collector and the lithium foil were laminated and rolled to such an extent that they were not separated to form a lithium metal layer.
[0121] Aluminum metal was sputter-deposited on the lithium metal layer to a thickness of 7 μm under vacuum to obtain a negative electrode.
[0122] <Comparative Example 3>
[0123] A commercially available copper current collector (I2B, Iljin Materials Co.) was prepared as a metal current collector substrate.
[0124] A lithium foil (Li foil, thickness: 20 μm) was placed in opposition to one surface of the copper current collector, and then the current collector and the lithium foil were laminated and rolled to such an extent that they were not separated to form a lithium metal layer.
[0125] Stainless steel metal was sputter-deposited on the lithium metal layer to a thickness of 7 μm under vacuum to obtain a negative electrode.
[0126] <Example 1>
[0127] A commercially available copper current collector (I2B, Iljin Materials Co.) was prepared as a metal current collector substrate.
[0128] A lithium foil (Li foil, thickness: 20 μm) was placed in opposition to one surface of the copper current collector, and then the current collector and the lithium foil were laminated and rolled to such an extent that they were not separated to form a lithium metal layer.
[0129] In addition, copper metal powder (average diameter (D50): 3 μm) and a binder (PVDF) were mixed in an NMP solvent at a weight ratio of 9:1 so that the volume ratio of solid content:NMP solvent was 5:5, thereby forming a protective layer slurry. The obtained slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 7 μm. Thus, the negative electrode was obtained.
[0130] <Example 2>
[0131] A negative electrode was obtained in the same manner as in Example 1, except that in Example 1, a mixture of copper metal powder (average diameter (D50): 3 μm) and silicon powder (particle size (D50): 3 μm) in a weight ratio of 5:5 was mixed with a binder (PVDF) in a weight ratio of 9:1 in an NMP solvent so that the volume ratio of solid component:NMP solvent was 5:5, thereby forming a protective layer slurry, and the prepared slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 7 μm.
[0132] <Example 3>
[0133] A negative electrode was obtained in the same manner as in Example 1, except that in Example 1, silicon powder (particle size (D50): 3 μm) and a binder (PVDF) were mixed in an NMP solvent in a weight ratio of 9:1 so that the volume ratio of solid component:NMP solvent was 5:5 to form a protective layer slurry, and the prepared slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 7 μm.
[0134] <Example 4>
[0135] A negative electrode was obtained in the same manner as in Example 1, except that in Example 1, aluminum powder (particle size (D50): 3 μm) and a binder (PVDF) were dispersed in an NMP solvent in a weight ratio of 9:1 so that the volume ratio of solid component:NMP solvent was 5:5, thereby forming a protective layer slurry, and the prepared slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 7 μm.
[0136] <Example 5>
[0137] A negative electrode was obtained in the same manner as in Example 1, except that in Example 1, copper metal powder (average diameter (D50): 500 nm) and silicon powder (average diameter (D50): 50 nm) were dispersed in an NMP solvent in a weight ratio of 5:5 so that the volume ratio of solid component:NMP solvent was 1:9 to form a dispersion, and the prepared dispersion was coated on the lithium metal layer and dried to form a protective layer with a thickness of 3 μm, which was rolled and laminated on the lithium metal.
[0138] <Example 6>
[0139] A negative electrode was obtained in the same manner as in Example 1, except that in Example 1, a mixture of copper metal wire (average diameter (D50): 500 nm, aspect ratio: 10) and silicon powder (average diameter (D50): 3 μm) in a weight ratio of 5:5 and a binder (PVDF) in a weight ratio of 9:1 were mixed in an NMP solvent so that the volume ratio of solid component:NMP solvent was 5:5, thereby forming a protective layer slurry, and the prepared slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 7 μm.
[0140] <Example 7>
[0141] A negative electrode was obtained in the same manner as in Example 1, except that in Example 1, a mixture of copper metal powder (average diameter (D50): 3 μm) and silicon filaments (average diameter (D50): 500 nm, aspect ratio: 10) in a weight ratio of 5:5 was mixed with a binder (PVDF) in a weight ratio of 9:1 in an NMP solvent so that the volume ratio of solid component:NMP solvent was 5:5, thereby forming a protective layer slurry, and the prepared slurry was coated on the lithium metal layer and dried to form a protective layer with a thickness of 7 μm.
[0142] <Experimental Example 1>
[0143] LiNi as the positive electrode active material 0.8 Mn 0.1 Co 0.1 O2, carbon black as a conductive material and polyvinylidene fluoride (PVdF) as a binder. The positive electrode active material: the conductive material: the binder were mixed in a weight ratio of 96:2:2, and NMP as a solvent was added to the resulting mixture to prepare a positive electrode active material slurry.
[0144] The positive electrode active material slurry was heated at 5.01 mAh / cm 2 The positive electrode was coated on each side of an aluminum current collector and then dried and calendered to obtain a positive electrode.
[0145] The electrolyte contains a solvent in which propylene carbonate (PC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1:2:1 (PC:DEC:DMC). The electrolyte is prepared, and the electrolyte contains 1M LiFSI, 1M LiPF6 and 30 wt% of fluoroethylene carbonate (FEC) in the total amount of the electrolyte.
[0146] A polyethylene separator (thickness: 20 μm) was inserted between the negative electrodes of Comparative Examples 1 to 3 and Examples 1 to 7 and the positive electrode, and then the electrolyte was injected, and CR2032 coin cells were manufactured according to a conventional method to obtain lithium metal batteries.
[0147] The prepared lithium metal battery was charged under the following conditions, and then the lithium metal battery was disassembled, and the thickness of the lithium electrodeposition layer formed on the negative electrode was calculated and shown in the following Table 1.
[0148] Charging: 0.2C, CC / CV, 4.25V, 1 / 20C cutoff
[0149] The thickness of the electrodeposited layer is calculated by selecting any two points and obtaining the average value of the thickness.
[0150] [Table 1]
[0151] Thickness(μm) Comparative Example 1 100 Comparative Example 2 65 Comparative Example 3 80 Example 1 50 Example 2 43 Example 3 42 Example 4 45 Example 5 41 Example 6 44 Example 7 43
[0152] Referring to Table 1, it can be confirmed that, in the case of the present disclosure, the electrodeposition thickness is significantly reduced.
[0153] On the other hand, it can be confirmed that when no protective layer is formed or the protective layer is formed by a deposition method, the electrodeposition thickness is not sufficiently reduced. This is because when the protective layer is formed by a deposition method, its porosity is insufficient.
[0154] <Experimental Example 2>
[0155] In order to understand the extent of reaction of negative electrode lithium with the atmosphere during the battery assembly process, lithium metal batteries were manufactured in the same manner as described in Experimental Example 1, but they were manufactured at a dew point of -20°C and the 1 KHz Hioki resistance was measured before activation. The results are shown in Table 2 below.
[0156] [Table 2]
[0157] Resistance(Ω) Comparative Example 1 2.59 Comparative Example 2 1.20 Comparative Example 3 2.01 Example 1 1.15 Example 2 1.19 Example 3 1.22 Example 4 1.21 Example 5 1.11 Example 6 1.18 Example 7 1.18
[0158] Referring to Table 2, it can be confirmed that when a protective layer is applied on the lithium metal, the reaction with the atmosphere is reduced and the battery internal resistance (measured by 1 kHz Hioki resistance) is small.
[0159] <Experimental Example 3>
[0160] In addition, the area is 6.25cm 2 The lithium metal battery manufactured under the conditions of Experimental Example 1 except for the single cell manufacturing was charged and discharged 200 times under the following conditions, and then the 200th discharge capacity retention rate relative to the 1st discharge capacity was calculated, and the results are shown in the following Table 3.
[0161] Charging: 0.2C, CC / CV, 4.25V, 1 / 20C cutoff
[0162] Discharge: 0.5C, CC, 3.0V, cut-off
[0163] [Table 3]
[0164]
[0165] Referring to Table 3, it can be confirmed that, as shown in Table 1, as the electrodeposition thickness becomes thinner, the life of Examples is extended.
[0166] In addition, it can be confirmed that, when formed as in the present disclosure, by having predetermined pores, the lithium in the lithium metal layer is smoothly dissolved to the outside of the protective layer, and there is an effect of improving the life characteristics, compared to forming by vapor deposition. When formed by vapor deposition, there are almost no pores, whereby lithium is difficult to dissolve and the degradation of life is accelerated. In addition, it can be confirmed that when stainless steel is used, the effect is more deteriorated than when aluminum is used.
[0167] In addition, it can be confirmed that the alloyable metal in the mixture of the metal and the alloyable metal reacts with the electrolyte by side reaction, and even if it is consumed, the metal remains and the protective layer can be maintained for a longer time, thereby the effect of extending the life is more excellent. It can be seen that the preferred form of the protective layer can also be obtained by preparing the protective layer by mixing powder and wire.
[0168] Based on the above disclosure, a person skilled in the art can make various applications and modifications without departing from the spirit and scope of the present disclosure.
[0169] Industrial Applicability
[0170] As described above, the negative electrode according to the embodiment of the present disclosure forms a protective layer on the lithium metal layer, thereby having the effect of minimizing the reaction of the lithium metal with the atmosphere and reducing resistance increase during the assembly process of the secondary battery.
[0171] In addition, the lithium metal battery comprising the negative electrode utilizes this protective alloying mechanism during actual charging and discharging, thereby minimizing the thickness of the lithium electrodeposition layer formed on the protective layer, increasing the electrodeposition density, thereby minimizing the side reactions of the electrolyte and improving the life characteristics.
Claims
1. A lithium metal battery, wherein an electrode assembly is constructed in a battery case together with a lithium non-aqueous electrolyte, wherein the electrode assembly comprises: negative electrode; a positive electrode having a structure in which a positive electrode mixture containing an active material is coated on at least one surface of a positive electrode current collector; and a separator, the separator being disposed between the negative electrode and the positive electrode, The negative electrode comprises: a metal current collector substrate, a lithium metal layer formed on at least one surface of the metal current collector substrate, a protective layer formed on the lithium metal layer, and a lithium electrodeposition layer formed by precipitating lithium on the protective layer, The protective layer comprises: a metal powder or wire comprising a metal selected from the group consisting of copper, stainless steel, nickel, and titanium; an alloyable metal powder or alloyable metal wire comprising an alloyable metal selected from the group consisting of Mg, Ca, Al, Si, Ge, Sn, Pb, Sb, Bi, Ag, Zn, Cd and Hg; or A mixture thereof, The thickness of the lithium electrodeposition layer is 0.1 to 50 μm. The protective layer is formed by coating on the lithium metal layer formed on at least one surface of the metal current collector substrate.
2. The lithium metal battery according to claim 1, wherein: The metal current collector substrate is one selected from the group consisting of copper, stainless steel, aluminum, nickel, titanium, copper surface-treated with a dissimilar metal, stainless steel surface-treated with a dissimilar metal, and aluminum-cadmium alloy.
3. The lithium metal battery according to claim 1, wherein: The metal current collector substrate is copper.
4. The lithium metal battery according to claim 1, wherein: The lithium metal layer has a thickness of 1 to 100 μm.
5. The lithium metal battery according to claim 1, wherein: The metal powder or metal wire contains metal copper or metal nickel.
6. The lithium metal battery according to claim 1, wherein: The metal powder of the protective layer and the alloyable metal powder each have a diameter of 1 nm to 30 μm.
7. The lithium metal battery according to claim 1, wherein: The metal wires and the alloyable metal wires of the protective layer each have a diameter of 1 nm to 30 μm, and a wire length / wire diameter ratio of 3 or more.
8. The lithium metal battery according to claim 1, wherein: The protective layer is a mixture of metal powder or metal wire and alloyable metal powder or alloyable metal wire.
9. The lithium metal battery according to claim 1, wherein: The thickness of the protective layer is 0.1 μm to 100 μm.
10. The lithium metal battery according to claim 1, wherein: The protective layer has a porosity of 1% to 70%.
11. The lithium metal battery according to claim 1, wherein: The protective layer also includes an adhesive and a conductive material.
12. A method for manufacturing a lithium metal battery according to claim 1, the method comprising the steps of: (a) forming a lithium metal layer on at least one surface of a metal current collector substrate; (b) mixing metal powder or metal wire, alloyable metal powder or alloyable metal wire, or a mixture thereof with a solvent to prepare a slurry, wherein The metal powder or wire comprises a metal selected from the group consisting of copper, stainless steel, nickel and titanium, The alloyable metal powder or alloyable metal wire comprises an alloyable metal selected from the group consisting of: Mg, Ca, Al, Si, Ge, Sn, Pb, Sb, Bi, Ag, Zn, Cd and Hg; and (c) coating the slurry on the lithium metal in step (a) and drying to form a protective layer, thereby manufacturing a negative electrode, The powder or filament of step (b) has a diameter of 1 μm to 30 μm.
13. A method for manufacturing a lithium metal battery according to claim 1, the method comprising the steps of: (a) forming a lithium metal layer on at least one surface of a metal current collector substrate; (b) dispersing metal powder or metal wire, alloyable metal powder or alloyable metal wire, or a mixture thereof in a solvent to prepare a dispersion, wherein The metal powder or wire comprises a metal selected from the group consisting of copper, stainless steel, nickel and titanium, The alloyable metal powder or alloyable metal wire comprises an alloyable metal selected from the group consisting of: Mg, Ca, Al, Si, Ge, Sn, Pb, Sb, Bi, Ag, Zn, Cd and Hg; and (c) coating the dispersion on the lithium metal in step (a) and drying to form a protective layer, thereby manufacturing a negative electrode, The powder or wire of step (b) has a diameter of 1 nm to 1000 nm.
14. The method for manufacturing a lithium metal battery according to claim 12 or 13, wherein: The slurry or dispersion is prepared such that the solid content of the metal powder, metal wire, alloyable metal powder or alloyable metal wire in the slurry or dispersion accounts for 0.1 to 80 volume % based on the total volume of the slurry or dispersion.
Citation Information
Patent Citations
Spring back inspection improvement system
KR1020200144667A
Packaging apparatus capable of aligning inner paper to cushion paper easily
KR1020210146015A
Lithium secondary battery negative electrode including protection layer made of conductive fabric, and lithium secondary battery including same
CN109792044A
Negative electrode for lithium ion secondary battery
JP2012009209A
KR20190057966A